KUALITAS RUANG TERBUKA HIJAU (RTH) PRIVAT PADA RUMAH TINGGAL DI DESA PEGUYANGAN KANGIN DITINJAU DARI SEGI EKOLOGIS - KADEK PUTRA SANTIKA NARAYANA; ANAK AGUNG BAGUS BAYU ANGGAWIRYA; IDA AYU CRI VINANTYA LAKSMI (GANEC SWARA, 2024)
Population growth results in increasing demand for residential space and built-up land. This will have an impact on the environment, namely reducing the quality of green open spaces in carrying out ecological functions. As happened in Denpasar City, one of which is in the North Denpasar area. The availability of green open space in Denpasar City is dominated by private green open spaces originating from residential areas, namely residential yards. However, as in the Peguyangan Kangin Village Area, even though it is dominated by residential areas where land use is privately owned, the provision of private open space is actually very minimal. It is feared that this dynamic will have a negative impact on the surrounding environment in the future. Therefore, it is important to carry out this research with the aim of analyzing the quality of private green open space in terms of its ecological function and the availability of private green open space in the Peguyangan Kangin Village area. This research uses a qualitative method with a descriptive approach. The object of research will focus on private green open space in residential yards in Peguyangan Kangin Village. The research results show that in general the quality of private green open space in residential yards in the Peguyangan Kangin area is not optimal, both in terms of area and vegetation in carrying out ecological functions. The research results also show that there are several factors that influence the quality of private green open space, one of the most dominant of which is land availability.